Decreased CD1a+, CD83+ and factor XIIIa+ dendritic cells in cervical lymph nodes and palatine tonsils of AIDS patients. Issue 2 (6th November 2013) - Gondak, Rogério; Mauad, Thais; Schultz, Luciana; Soares, Fernando; Kowalski, Luiz P; Vargas, Pablo A
<x xml:space="preserve">Abstract</x> Aims The purpose of this study was to quantify and compare the density of dendritic cells (DCs) in cervical lymph nodes (LNs) and palatine tonsils (PTs) of AIDS and non‐AIDS patients. Methods and results Factor XIIIa, CD1a and CD83 antibodies were used to identify migratory DCs by immunohistochemistry in LNs and PTs of 32 AIDS patients and 21 HIV‐negative control patients. Quantification was performed by the positive pixel count analytical method. AIDS patients presented a lower density of factor XIIIa+ cells (P < 0.001), CD1a+ cells (P < 0.05) and CD83+ cells (P < 0.001) in cervical LNs and PTs compared to the non‐AIDS control group. Conclusion Overall depletion of DCs in lymphoid tissues of AIDS patients may be predictive of the immune system's loss of disease control.